Electrocoagulation treatment of raw palm oil mill effluent : Optimization process using high current application - Mohd, Nasrullah; Ansar, Sabah; Krishnan, Santhana; Singh, Lakhveer; Gouse Peera, S. Gouse; Zularisam, Abdul Wahid (Elsevier Ltd, 2022)
In the electrocoagulation wastewater treatment process, extremely polluted water treatment requires an effective technique, and using high current is one of those. This study aims to optimize electrocoagulation parameters such as operation time, electrodes gap and the initial pH by applying high current intensity to treat palm oil mill effluent (POME) via Box–Behnken design (BBD) method. Chemical oxygen demand (COD), biological oxygen demand (BOD), and suspended solids (SS) were used as the response variables in the quadratic polynomial model. Most of the selected models in the analysis of variance (ANOVA) have shown significant results. A high connection between the parameters and dependent variables was surprisingly discovered in this study which the obtained value of R2 for removal percentage of COD, BOD and SS were 0.9975, 0.9984 and 0.9979 respectively. Optimal removal was achieved at 19.07 A of current intensity (equivalent to 542 mA/cm2 of current density), 44.97 min of treatment time, 8.60 mm of inter-electrode distance and 4.37 of pH value, resulted in 97.21%, 99.26% and 99.00% of COD, BOD and SS removal respectively. This optimized scheme of operating parameters combination offers an alternate choice for enhancing the treatment efficiency of POME and also can be a benchmark for other researchers to treat highly polluted wastewater.